Photodetectors: Ultrasensitive and Broadband MoS2 Photodetector Driven by Ferroelectrics (Adv. Mater. 42/2015). (6th November 2015) - Wang, Xudong; Wang, Peng; Wang, Jianlu; Hu, Weida; Zhou, Xiaohao; Guo, Nan; Huang, Hai; Sun, Shuo; Shen, Hong; Lin, Tie; Tang, Minghua; Liao, Lei; et al.
Abstract : Ultrasensitive and broadband MoS2 photodetectors driven by ferroelectrics are developed by J. Wang, W. Hu, and co‐workers on page 6575. A high detectivity (≈2.2 × 10 12 Jones), photoresponsitivity (2570 A W −1 ), and photoresponse wavelength (visible to 1.55 μm) detector is achieved under an ultra‐high electrostatic field from ferroelectric polarization.